Enhanced Photoluminescence of 1.3μm InAs Quantum Dots Grown on Ultrathin GaAs Buffer/Si Templates by Suppressing Interfacial Defect Emission - Kim, Yeonhwa; Chu, Rafael Jumar Abella; Ryu, Geunhwan; Woo, Seungwan; Lung, Quang Nhat Dang; Ahn, Dae-Hwan; Han, Jae-Hoon; Choi, Won Jun; Jung, Daehwan (American Chemical Society, 2022)
We report on the photoluminescence enhancement of 1.3 mu m InAs quantum dots (QDs) epitaxially grown on an ultrathin 250 nm GaAs buffer on a Si substrate. Decreasing the GaAs buffer thickness from 1000 to 250 nm was found to not only increase the coalesced QD density from 6.5 x 108 to 1.9 x 109 cm-2 but also decrease the QD photoluminescence emission intensity dramatically. Inserting an Al0.4Ga0.6As potential barrier layer maintained strong photoluminescence from the QDs by effectively suppressing carrier leakage to the GaAs/Si interfacial region even when the GaAs buffer was thinned to 250 nm. We then fabricated a light-emitting diode using the ultrathin 250 nm GaAs buffer on Si and confirmed strong electroluminescence peaking at 1.28 mu m without interfacial defect emission at room temperature. We believe that this work is promising for monolithically integrated evanescent Si lasers using InAs/GaAs QDs.